Study of India’s Rural Development through Renewable Energy Sources - Dr. Pawan Kumar (International Journal of Engineering and Management Research, 2022)
The rural sector, which is home to the majority of the country's people, must be strengthened if the country is to progress. Infrastructure, village electricity, mechanisation, and other methods should all be employed to make development. Villages in several states face a challenge with centralised generation and distribution systems since grid access is either impossible or too expensive. Power generating, cooking, irrigation, and water heating in rural areas can all benefit from renewable energy sources found in nature. The Indian government has come up with fresh plans and financial assistance for the implementation of such projects at the national and state levels. There are various technologies that can be used to improve the quality of life in rural areas.